Limbah Plat Kontainer Sebagai Bahan Dasar Perancangan Produk Interior Kantor - Geraldine, Dinda; Mulyono, Grace (Intra, 2019)
This design was carried out to determine the potential of the wasted container plate to be used as the main material of interior products. More and more wasted container plates are generated from the construction of container offices which always end to be melted into scrap metal. The characteristic of container as well as the background of the sustainable concept that want to be emphasized also affect the final design. This design is using the design thinking method where the analysis of both material and user is done to underlie the final design. Direct experiments with the materials are also carried out to produce good construction. Flatpack and modular were chosen as the main aspects in designing interior products for this office furniture. Containers have good strength and robustness, but there are some design limitations because of their unique shape and it becomes another challenge to develop this material that is quite new in the world of furniture, which still has more potential to be explored. The advantages of containers itself are used to offset some of this material's shortcomings.